Lignin relocation contributed to the alkaline pretreatment efficiency of sweet sorghum bagasse. (15th October 2015) - Yan, Zhipei; Li, Jihong; Chang, Sandra; Cui, Ting; Jiang, Yan; Yu, Menghui; Zhang, Lei; Zhao, Gang; Qi, Panlun; Li, Shizhong
Highlights: The relocation of LCC occurred in Ca(OH)2 pretreatment. Complex formation of LCC and Ca 2+ resulted in the relocation. Lignin did not adsorb cellulase during enzymatic hydrolysis. Abstract: Sodium hydroxide and calcium hydroxide are used to improve enzymatic hydrolysis of lignocellulose. Compared to NaOH, less carbohydrates was lost in Ca(OH)2 pretreatment. It was found that the substrates with similar lignin content prepared from NaOH and Ca(OH)2 pretreatments had distinct cellulose conversion rate. To understand the mechanism of action, two sweet sorghum bagasse (SSB) samples with similar lignin content were prepared. The enzymatic hydrolysis result showed that the cellulose conversion rate of SSB treated by Ca(OH)2 was about 1.62 times that of SSB treated by NaOH. SEM results showed tiny droplets on the SSB surface pretreated with Ca(OH)2 . EDS analysis revealed that the droplets were a complex of lignin–carbohydrate and calcium ions. The results suggested that Ca(OH)2 not only increased the porosity of substrates, but also reduced carbohydrates loss by forming a complex with lignin and calcium ions. This demonstrated that calcium ions could be used to reduce the carbohydrates loss from the pretreatment procedure.